The influence of socio-economic status on test performance and the relationship of subjective well-being on socio-economic status and test performance of UPV-CAS freshmen students of SY 1998-1999. - Flamiano, Eden
The aims of this study were to investigate the effects of socio-economic status on test performance and the relationship between subjective well-being and socio-economic status (SES), as well as the relationship between subjective well-being (SWB) and test performance (TP) of students. Participants of this study were 74 freshmen released STFAP grantees of UPV-CAS of the S.Y. 1998-99. The respondents were chosen randomly from the entire list of first year students and were identified purposively based on their income brackets. Participants were given a reading comprehension article to be read for 5 to 6 minutes, after the alloted time, the article was collected whether the participants have finished reading or not. Another questionanire was given to measure their subjective well-being. Economic status was determined through the use of the assigned STFAP brackets and the annual income of the participant's parents. The one way-ANOVA for socio economic status and test performance was F(72-2.44,p<.05, indicating that socio economic status did not affect test performance. The Pearson product moment correlation for socio economic status in relation to subjective well-being was r=.012,p<.0, suggesting that socio-economic status was not related to subjective well-being of the students. However, the correlation between subjective well-being and test performance was r=.416,p<.o5, indicating that there was a significant relationship between the two variables. The findings of the study suggest that socio-economic status has weak or no relationship with subjective well-being of the First year students. it also did not influence the students test performance. However, the subjective well-being, or the outlook in life of the students has a relationship with their test performance in school. Therefore, it was concluded that socio-economic status would not be a hindrance for a better performance in school but subjective well-being would affect the output of the student's performance.